Serial position effects in the Logical Memory Test: Loss of primacy predicts amyloid positivity. Issue 3 (4th December 2020) - Bruno, Davide; Mueller, Kimberly D.; Betthauser, Tobey; Chin, Nathaniel; Engelman, Corinne D.; Christian, Bradley; Koscik, Rebecca L.; Johnson, Sterling C.
Abstract : Background: Story recall is a frequently used neuropsychological test of episodic memory with clinical populations and for screening participants in drug trials for Alzheimer's disease. However, it is unclear at this stage which underlying mechanisms confer the test its sensitivity. In this paper, we examined serial position effects, that is, better recall for items learned early and late on a list, in story recall, and their usefulness to predict early changes associated with neurodegenerative markers. Methods: We analysed data from the Wisconsin Registry for Alzheimer's Prevention. First, we tested whether serial position effects were present in story recall (measured with the Wechsler Memory Scale Logical Memory Task; LMT) across individuals who were classified as cognitively unimpaired – stable, cognitively unimpaired – declining, or as having mild cognitive impairment (MCI). Results: Our results showed clear serial position effects for all groups, except for delayed recall among individuals with MCI, where no primacy effect was observed. Second, we tested whether loss of primacy from immediate to delayed recall was associated with amyloid burden (as measured with PiB PET) in individuals who were cognitively unimpaired at baseline. We found that more primacy loss predicted amyloid positivity, above and beyond the LMT total score. Conclusions: This report is the first to show that loss of primacy between immediate and delayed story recall is associated with amyloid burden.